Factors to determine shariah audit quality in Islamic financial institutions: evidence from Malaysia / Kamariah Ali - Ali, Kamariah (2012)
The main objective of this study is to examine the significant factors that determine the shariah audit quality of IFIs in Malaysia. In this study a survey questionnaires has been employed for source of information in order to analyze the relationship between shariah audit quality and factors that determine the shariah audit quality. The shariah audit quality is the dependent variable and this is measured through recommendation given by shariah auditors and the services provided by shariah auditors. ndependent variables consist of items such as competence of shariah auditor, shariah compliance process, standard and guidelines used and scope of shariah audit. The results indicate that there are no significant relationships between independent variables and the dependent variable as all the hypotheses show no significant relationships. The findings indicate the fact that the term shariah audit is not taken so seriously by responsible quarters due to lacking in regulatory framework as well as governance structure. Hence, extensive further research on the matter needs to be looked into by the practitioners of Islamic financial institutions as well as the regulatory bodies.